Kinetic study on pyrolysis and combustion of palm Empty Fruit Bunches (EFB) by using TGA analysis - Daud, W.M.A.W.; Aroua, M.K.; Ho, Y.T.; Tan, A.B. (2008)
Pyrolysis and combustion of palm empty fruit bunches (EFB) were studies by using thermogravimetric analyzer (TGA). The non-isothermal pyrolysis of EFB was performed from ambient temperature up to 900 C at heating rates of 5, 15, 30 and 40 C/min in N2 atmosphere. The apparent activation energy of pyrolysis varied linearly with heating rate. The kinetics of EFB combustion is investigated by means of isothermal TGA and measurements were carries out for different fixed temperatures between 500 C and 700 C in O2 atmosphere. The isothermal and non-isothermal conditions allow the kinetic constants (activation energy, pre-exponential factors and order of reaction) to be estimated by means of the analytical solution of the mass conservation equations. Thermal degradation rates inthe first reaction zone were significantly higher than those in the second reaction zone. The apparent activation energies were in the range of 117.25-120.16 kJ/mo1 and 17.767 kJ/mo! for the pyrolysis and combustion respectively. The frequency factor, A for pyrolysis ranged from 4.24x10 8s -1 to 1.33x10 9s-1. And for combustion, frequently factor was 1.08x10 -1s-1.